2005
DOI: 10.1055/s-2005-860988
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Pancreatic Stenting in Severe Chronic Pancreatitis

Abstract: The majority (70 %) of patients with severe chronic pancreatitis who respond to pancreatic stenting maintain this response after definitive stent removal. However, a significantly higher re-stenting rate was observed in patients with chronic pancreatitis and pancreas divisum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(98 citation statements)
references
References 8 publications
(20 reference statements)
0
90
0
5
Order By: Relevance
“…Early removal of a pancreatic stent can be considered if it has no effect on pain. Currently there are two strategies in pancreatic stenting: either removing the pancreatic stent after a period of 6−12 months irrespective of the resolution of the stricture of the main pancreatic duct or substitution of pancreatic stents until stricture disappearance [175,176,[193][194][195][196][197][198][199][200]. Long-term pain relief was experienced by two-thirds of patients after 12 months stenting, though resolution of the stricture was observed in a minority of patients [176,193].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Early removal of a pancreatic stent can be considered if it has no effect on pain. Currently there are two strategies in pancreatic stenting: either removing the pancreatic stent after a period of 6−12 months irrespective of the resolution of the stricture of the main pancreatic duct or substitution of pancreatic stents until stricture disappearance [175,176,[193][194][195][196][197][198][199][200]. Long-term pain relief was experienced by two-thirds of patients after 12 months stenting, though resolution of the stricture was observed in a minority of patients [176,193].…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…Insertion of a pancreatic stent is indicated in case of dominant main pancreatic duct stricture (prepapillary stricture with upstream dilation). Current strategy calls for unscheduled stent replacement when patients become symptomatic (abdominal pain) and pancreatic duct dilation is shown by abdominal ultrasound or MRCP [175,[193][194][195][196]. Early removal of a pancreatic stent can be considered if it has no effect on pain.…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…This procedure with ERCP allows putting in place the transpapillary endoprotesis as drainage. In addition, the transluminal stones removal and/or lithotripsy can be possible, if intraductal stones are present [60][61][62]. The surgical management has shown good results in the treatment of chronic pseudocysts, pancreatic duct dilatation with stenosis, and stones.…”
Section: Chronic Pseudocystsmentioning
confidence: 99%
“…It is important to note, however, that after stent removal the rate of recurrence of a main PD stricture is high. In fact, Eleftherladis et al [39] reported the stricture relapse rate after a 2 year follow up period was as high as 38%, with these patients require repeat stenting.…”
Section: Pancreatic Stricturesmentioning
confidence: 99%
“…Two years after intervention, they noted a similar decrease in the number of pain episodes per year. As such, it was concluded that [39] 100 70 69 70 Rosch et al [35] 1018 88 60 85 Eisendrath et al [104] 100 100 69 70 Layer et al [105] 66 NA 36 50 Cremer et al [106] 75 NR 37 94…”
Section: Pancreatic Stonesmentioning
confidence: 99%